FORAGE YIELD AND NUTRITIVE QUALITY OF BRACHIARIA MULATO II INFLUENCED BY NPK FERTILIZER RATES AND AGE OF RE-GROWTH IN SHIKA NORTHERN GUINEA SAVANNAH OF NIGERIA - Ahmed, S. A.; Abdu, S.B.; Amodu, J. T.; Hassan, M.R.; Sani, R.T.; Salisu, S.G.; Abdullahi, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Two years agronomic trial were conducted on a one-year-old established Brachiaria Mulato II pasture to evaluate the regrowth pattern, seasonal herbage yield (Dry matter yield) and nutritive quality. The treatments consisted of NPK 20:10:10 fertilizer (applied at different rates of 0, 50, 100, 150, and 200 kgha) and stages of re-growth (at 8,10 and 12 weeks respectively) these were laid in a split plot design with 5 x 3 factorial arrangement. The main plots were NPK 20:10:10 fertilizer, while stages of re-growth were allocated to the sub-plots. The result shows that, dry forage yield was significantly (P<0.05) affected by the rates of fertilizer application. The highest yield (6.08t/ha) was recorded at 200 kgha-1 rate. Ages of regrowth significantly (P<0.05) affected the Dry forage yield (7.96t/ha) at 12 weeks. Organic matter content was significantly (P<0.05) higher (82.50%) at 150 kgha-1 rate of application. Crude protein was significantly (P<0.05) higher (8.33%) at 100 kgha-1 rate which was at par with 0 kgha-1 (8.30%) and (8.04%) at 200 kgha-1 application rates. Age of regrowth showed a significantly (P<0.05) higher Crude protein content at 8 weeks (9.32%) compared to other weeks. The total digestible nutrients (TDN) was significant (P<0.05) difference across the weeks with the highest value recorded at 12 weeks (47.51%) compared to other weeks. Neutral detergent fibre (NDF) was significantly (P<0.05) higher at 10 weeks (64.69%) while acid detergent fibre (ADF) was significantly (P<0.05) higher at 12 weeks (39.77%) compared to the other weeks. Calcium concentration with application of fertilizer ranged between (0.363- 0.527%) and Phosphorus (0.176- 0.188%). With age of regrowth, calcium content of the forage ranged between (0.395-0.517%) while phosphorus had value ranges of 0.128-0.211%. Iron (2698.7ppm) and Cobalt (224ppm) were significantly (P<0.05) higher at 50kgha-1 application rate. Age of regrowth significantly (P<0.05) affected both Iron and Cobalt concentration at 12 weeks of age (2555.90 and 225.20 ppm). It was therefore concluded that application of NPK 20:10:10 fertilizer at the rate of 200 kgha-1 rate produced the highest Dry matter yield. Harvesting of forage at 8 weeks of regrowth increased the nutritive quality by 39.26%. Also harvesting the forage material at 12 weeks’ increases yield and higher mineral concentrations. Pasture producers and livestock farmers can practically apply 200kgha-1 NPK (20:10:10) fertilizer (4 bags) on regrowth of Brachiaria Mulato II and harvest at 8 weeks for better nutritive quality and 12 weeks for higher dry matter yield and returns.